Effects of Multi-Generational Soft Diet Consumption on Mouse Craniofacial Morphology - Hassan, Mohamed G.; Kaler, Harjot; Zhang, Bin; Cox, Timothy C.; Young, Nathan; Jheon, Andrew H. (Frontiers in Physiology, 2020)
Variations in craniofacial morphology may arise as a result of adaptation to different environmental factors such as soft diet (SD), which lessens functional masticatory load. Prior studies have shown that changes in the masticatory muscle function associated with a switch to short-term SD led to changes in craniofacial morphology and alveolar bone architecture. However, the long-term effects of SD and the associated adaptive changes in craniofacial shape are unclear. Our novel study set out to profile prospective skull changes in mice fed SD over multiple generations using three dimensional (3D) geometric morphometric analysis (GMA). Our results revealed that short-term SD consumption led to a significant decrease in craniofacial size, along with numerous shape changes. Long-term SD consumption over 15 continuous generations was not associated with changes in craniofacial size, however shape analysis revealed mice with shortened crania and mandibles in the anteroposterior dimension, as well as relative widening in the transverse dimension compared to the average shape of all mice analyzed in our study. Moreover, changes in shape and size associated with different functional loads appeared to be independent - shape changes persisted after diets were switched for one generation, whereas size decreased after one generation then returned to baseline size. Our study is the first to study the role of prolonged, multi-generational SD consumption in the determination of craniofacial size and shape.